Dynamics of cerebral metabolism in patients with chronic subdural hematoma evaluated with phosphorous 31 MR spectroscopy before and after surgery. - Yoshida, K; Furuse, M; Izawa, A; Iizima, N; Hirano, T; Kuchiwaki, H; Inao, S; Sugita, K (American Journal of Neuroradiology, 1994)
PURPOSE To determine whether the depression of cerebral bioenergetic metabolism caused by chronic subdural hematomas can account for neurologic dysfunction and whether the degree of metabolic depression may be useful for clinical assessment and therapy. METHODS Sixteen patients who had chronic subdural hematomas with hemiparesis and/or mental disturbances underwent phosphorous 31 MR spectroscopy before and 10 to 14 days after surgery. Phosphorous 31 MR spectroscopy was also performed on 5 patients who had chronic subdural hematomas with only slight headaches who were treated by conservative therapy and on 10 healthy volunteers. RESULTS The peroperative phosphocreatine-to-inorganic phosphate ratio (2.10 +/- 0.36) improved to normal values (2.69 +/- 0.44) after evacuation of hematomas. This improvement was accompanied by complete disappearance of hemiparesis and/or mental disturbance. Brain tissue pH also improved from 7.07 +/- 0.11 to 7.205 +/- 0.13 after surgery. On the other hand, patients who had chronic subdural hematomas with only slight headaches had the same phosphocreatine-to-inorganic phosphate ratio and brain intracellular pH as healthy volunteers. CONCLUSION The phosphocreatine-to-inorganic phosphate ratio may be useful for determining when to operate on patients with chronic subdural hematomas and to assess the efficacy of treatment.